Perilaku Pencarian Informasi Mahasiswa Ilmu Perpustakaan Dan Informasi Islam Dalam Menyusun Skripsi - Oktaria, Novi; Kesuma , Mezan el Khaeri; Yunita, Irva; RA, Okta Reni (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Understanding the process of information seeking is essential to support the effectiveness of undergraduate thesis writing among students. This study aims to analyze the information-seeking behavior of Library and Information Science students from the 2021 cohort who are currently working on their final projects, using David Ellis’s model as the analytical framework. A qualitative approach was employed through interviews with eleven students. The results show that most respondents engaged in nearly all stages of Ellis’s model, including starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending. Starting and browsing were the most frequently performed stages, while chaining and verifying were less consistently applied. These variations were influenced by students’ information literacy levels, individual search strategies, and access to information sources. Several challenges were identified, such as lack of training in using academic databases, time constraints, and academic workload. These findings highlight the importance of enhancing students' information literacy through structured training or librarian-led guidance to support more effective information seeking in thesis writing.